2016
DOI: 10.1186/s12940-016-0134-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal levels of endocrine disruptors, polybrominated diphenyl ethers, in early pregnancy are not associated with lower birth weight in the Canadian birth cohort GESTE

Abstract: BackgroundPolybrominated diphenyl ethers are known endocrine disrupting environmental contaminants used as flame retardants. Their levels have increased in humans over the last ten years, raising concerns about their consequences on human health. Some animal studies suggest that PBDEs can affect fetal growth; however, the results of human studies are contradictory. This study evaluates the association between the most common PBDEs in maternal blood measured in early pregnancy and birth weight.MethodsBDE-47, BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…For example, a meta-analysis by Govarts et al (2016), found an association between PCB 153 and low birth weight [ 21 ] whereas Lenters et al [ 18 ] did not find an association. Similar inconsistent associations exist for phthalates and BPA [ 22 24 ], OCPs [ 18 , 25 ] and PBDEs [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 81%
“…For example, a meta-analysis by Govarts et al (2016), found an association between PCB 153 and low birth weight [ 21 ] whereas Lenters et al [ 18 ] did not find an association. Similar inconsistent associations exist for phthalates and BPA [ 22 24 ], OCPs [ 18 , 25 ] and PBDEs [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 81%
“…In this case, results were also discordant. Serme-Gbedo et al [54] evaluated nine epidemiological studies assessing the relationship between PBDEs and birth weight, and four reported a negative association, while two reported a non-significant negative association, two others reported no statistically significant association, and one reported a negative association for male infants only, and a positive association for female newborns only.…”
Section: From Placenta To Newbornmentioning
confidence: 99%
“…In regions where the exposure to PBDEs is higher than the US Environmental Protection Agency Reference dose, exposures have reported a positive correlation between PBDE exposure and birth weight and length,103 while other regions have shown the opposite relationship104107 or no relationship at all 96,108. Furthermore, postnatal exposures to maternal PBDEs through breast milk continue to be a significant source of PBDE congeners.…”
Section: Household Exposuresmentioning
confidence: 99%